Effects of the invasive species Poecilia gillii (Cyprinodontiformes: Poeciliidae) on Pseudopoecilia fria in coastal rivers of the Choco region, Ecuador - Jiménez Prado, Pedro Jorge; Vásquez, Fernando; Rodríguez-Olarte, Douglas; Taphorn, Donald (Revista de Biología Tropical, 2020)
One of the causes contributing to the decrease of biodiversity is the introduction of exotic species that often end up being invasive, and end up competing with local species. This competition is not always "fair" since invaders commonly have adaptive advantages that give them an advantage over local species. This study was carried out in small watersheds in northwestern Ecuador and identifies the effects of the recent introduction of P. gillii on the native species P. fria; using population analysis (longitudinal distribution, growth parameters and morphometry). The results show a displacement of P. fria towards the upper part of the river, acceleration in its growth and therefore an earlier sexual maturity with a consequent decrease in body size and finally a change in body depth with posterior displacement of the pectoral fin.